PENGARUH BIMBINGAN KELOMPOK TEKNIK TALKING CHIPS TERHADAP PENGAMBILAN KEPUTUSAN KARIR PADA SISWA SMA - Nengsih, Widia; Handayani, Arri; Rakhmawati, Ellya (Al-Isyraq: Jurnal Bimbingan, Penyuluhan, dan Konseling Islam, 2026)
This study aims to analyze the effect of group guidance services using the talking chips technique on the career decision-making abilities of eleventh-grade students at SMA Laboratorium School UPGRIS. This study used a quantitative approach with a quasi-experimental method and a one-group pretest–posttest design. The sample consisted of 10 students selected through purposive sampling based on the results of the Student Needs Assessment (AKPD) and interviews with guidance and counseling teachers. The research instrument was a career decision-making questionnaire, which had been tested for validity and reliability. The results showed that the average posttest score was higher than the pretest score. The results of the hypothesis test using a paired sample t-test showed a significance value of 0.000 0.05, indicating a significant difference between the pretest and posttest scores. Thus, group guidance services using the talking chips technique have a positive effect on improving students' career decision-making abilities.